The Influence of Occupational Safety and Health (OSH) Culture and Management Commitment on Occupational Safety and Health Management System (OSHMS) Performance through Employee Job Satisfaction at PT Aimtopindo Nuansa Kimia - Edward Alexander; Agus Triyono (CV. Publikasi Indonesia, 2026)
The oil and gas industry is characterized by a high level of occupational accident risk, making the implementation of an OSHMS essential for improving workplace safety, productivity, and organizational sustainability. This research aims to examine the influence of Occupational Safety and Health culture and management commitment on OSHMS performance through employee job satisfaction at PT. Aimtopindo Nuansa Kimia. A quantitative research approach with a survey method was employed. Primary data were collected through questionnaires and interviews, while secondary data were obtained from relevant literature and company documents. The data were analyzed using the SEM-PLS approach with SmartPLS software. The findings indicate that both OSH culture and management commitment have a positive and significant effect on employee job satisfaction. Job satisfaction also has a positive and significant effect on OSHMS performance. The direct effect of OSH culture on OSHMS performance is not significant; however, it has a significant indirect effect through job satisfaction, indicating full mediation. In contrast, management commitment has both a significant direct effect on OSHMS performance and an indirect effect through job satisfaction, indicating partial mediation. Furthermore, management commitment is identified as the most dominant factor influencing OSHMS performance. This study finds that OSHMS success relies on safety culture, management commitment, and job satisfaction. Therefore, the company is advised to strengthen its safety culture through continuous training and reward programs, enhance management commitment with effective communication and regular evaluations, and improve employee job satisfaction by offering career development, competency building, and fair incentives to ensure sustainable OSHMS implementation.